Dynamics of soil properties as influenced by rubber based agroforestry system in hilly zone of Karnataka - Kannur, Siddappa; Patil, S.J.; Inamati, S.S. (Indian Journal of Agroforestry, 2020)
The basic precept of agroforestry is its ability to maintain fertility of poor soil. Researchers always try to assess how different nutrients present in soil respond to the age levels and practices on tree and crop cultivation, and effect of application of different organic manures and biofertilizers to intercrops. Present study, aiming to assess the effect of different age levels and practices on rubber plant and nutrient management on bird’s eye chilli (BEC) on soil fertility status, was carried out. The age of rubber plantation and practices followed on rubber significantly influenced soil parameters. The plots treated with combined application of FYM, Azotobacter and phosphate solubilizing bacteria (PSB) registered highest values in terms of soil physical and chemical properties. Interactions were non-significant for most of the soil parameters. Thus, combined use of FYM, Azotobacter and PSB on BEC under organic practice on rubber in two-years old rubber plantation proved better in improving soil fertility under agroforestry system.